Feedback Support for Training: Accounting for Learner and Task - McLaughlin, Anne Collins (Proc Hum Factors Ergon Soc Annu Meet, 2008)
Years of research on feedback has not produced universal prescriptions for feedback during training. Results are split in two directions; those recommending more feedback during training and those recommending less. This has resulted in no unified theory and little understanding of other factors that might affect feedback mechanisms. The current experiment manipulated the cognitive load of the task and measured the working memory capacities of the learners to see whether forcing the learner to self-evaluate affects learning of a cognitive task and how this might be moderated by learner ability and task load. Results generally showed that reducing task load through supportive feedback resulted in more learning.